AN Unsilenced Text: - El Batran, Mariam Mounir (AUC Knowledge Fountain, 2019)

(untitled)
This thesis provides a critical reading of Hanan al-Shaykh’s novel Women of Sand and Myrrh and Leila Abouzeid’s novel Year of the Elephant, focusing on how the women in these stories seek to articulate and enact their own agency in the face of attempts to limit them. Recent critical literature, such as Lila Abu-Lughod’s book Do Muslim Women Need Saving? have sought to use microhistories of individual women to counter the stereotypical image of Arab women portrayed in contemporary media, including modern Arabic literature in translation. My study has a parallel focus that will introduce new stories and models of Arab women as alternatives to the stereotype of being weak and oppressed. I offer close readings of the texts that highlight the individuality of the protagonists, while placing these works in a cultural context that provides a better understanding of the individual experiences of these women.